Dissolved Phosphorus Losses by Lateral Seepage from Swine Manure Amendments for Organic Rice Production. Issue 3 (3rd May 2013) - Liang, X. Q.; Li, L.; Chen, Y.X.; Li, H.; Liu, J.; He, M.M.; Ye, Y.S.; Tian, G.M.; Lundy, Mark
Abstract : Because excessive P fertilizer application in rice ( Oryza sativa L.) systems leads to P losses in ambient waters, P management strategies that satisfy crop P demand while minimizing P loss are essential to productive and environmentally benign rice production. The main objective of this paddy field experiment was to measure the effects of organic fertilization via swine ( Sus scrofa ) manure on dissolved P losses by lateral seepage from organic rice production. Four swine manure organic amendment rates (0 [Ctr], 26 [Low], 39 [Middle], and 52 [High] kg P ha –1 ) were applied over the course of three rice growing seasons in 4‐ by 5‐m plots constructed to facilitate the measurement of total dissolved phosphorus (TDP) and reactive phosphorus (DRP) via lateral seepage and surface runoff. The TDP and DRP concentrations in the lateral seepage water increased with increasing amendment rates. Lateral seepage was one of the important pathways of P losses from organic paddy fields. The seasonal averages of TDP fluxes by lateral seepage varied from 1.95 to 4.30 g P m –1 (bund scale) and 0.39 to 0.86 g P m –2 (plot scale) among the amendment rates (from low to high), accounting for 13.0 to 15.6% of the total P applied. In addition, floodwater level acted as the main driving force for the P lateral seepage losses from paddy fields, with a positive linear relationship ( R 2 = 0.50) between floodwater level and daily lateral flow during the flooded periods ( P = 0.05). Based on these results, P lateral seepage losses from organic rice production system would be minimized by shallow floodwater management and low swine manure amendment.